(3QSGdI GdSGFd hGdeLjH hQhV fRgI GdCQjHs
(3ChdgG (B:s
(3GdMeO ddg hCTgO Gf SjOfG eMeO YHOg hQShdg GdPi CTQbJ HfhQ GdCfSGf aLQg GdUGOb Xde GdVdGdI s
(3BNQgG (B:s
(3eHJhQ hBNQ GdehLhO efgG(B: (3jbhd Gf GdeQGO HGdSaQ LedI hdh cGf ceG bdfG SJI CejGd hCfG Cbhd Gf GdSaQ GdPi Jcde Ydjg GdabgGA gh GdSaQ GdeQYj ddTQY s
(3fSNI KGfjI JJab ai ChdgG eY GdfSNI GdChdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B31 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeg (B- (3GdQHGW (B(1138 (3O(B) s
Keywords: (3GdCOHs